The Role of Immersion as a Mediator Between Visibility, Metavoicing, and Guidance Shopping on Purchase Intention - Putri, Adelia Kurnia; Syah, Muhammad Fahmi Johan (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The study aims to test the immersion variable as a mediator between visibility, metavoicing, and guidance shopping against purchase intention on Shopee's live-streaming shopping features. This type of research is quantitative with design correlation path analysis. A total of 114 respondents were millennials aged 17–20. Research results show that the immersion variable is a significant mediator variable between metavoicing and guidance shopping towards purchase intention. There is a significant direct influence between the visibility guidance shopping variable and the immersion on the purchase intention. However, the results of the analysis also show that the metavoicing variable does not have a direct effect on the purchasing intention, while visibility does not directly affect immersion. Therefore, the immersion variable is not the mediator variable between visibility and purchase intention. Based on that, purchase intention will increase significantly if there is an increase in metavoicing and guidance shopping. Metavoicing and guidance shopping increased the purchase intention with increased immersion. However, the buy intention will increase significantly without the increase in immersion, and the purchase intent will only rise significantly when the metavoicing variable is bridged by immersions.